Learning jQuery : create better interaction, design and web development with simple JavaScript techniques - Chaffer, Jonathan (Packt Publishing, 2011)
"Discover the new features available in jQuery 1.6 in this third update of this popular jQuery book"--Back cover
Keywords: JQuery (Computer file); JavaScript (Computer program language); Web site development.; Web sites -- Design.; Internet programming.; elektronické knihy; electronic books